2015
DOI: 10.1021/acschemneuro.5b00248
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Preliminary PET Imaging Studies of a FAAH Radiotracer ([11C]MPPO) Based on α-Ketoheterocyclic Scaffold

Abstract: Fatty acid amide hydrolase (FAAH) is one of the principle enzymes for metabolizing endogenous cannabinoid neurotransmitters such as anandamide, and thus regulates endocannabinoid (eCB) signaling. Selective pharmacological blockade of FAAH has emerged as a potential therapy to discern the endogenous functions of anandamide-mediated eCB pathways in anxiety, pain and addiction. Quantification of FAAH in the living brain by positron emission tomography (PET) would help our understanding of the endocannabinoid syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Based on the results of in vitro autoradiography and in vivo PET studies on rat brain, we speculated that insufficient brain permeability of [ 11 C]­QCA might be induced by ATP-binding cassette efflux transporters located at the blood–brain barrier, , particularly, P-glycoprotein (PgP, ABCB1) and breast cancer resistance protein (Bcrp, ABCG2). To test this hypothesis, we carried out PET imaging studies of [ 11 C]­QCA on wild-type and PgP/Bcrp knockout (ABCB1a/1b –/– ABCG2 –/– ) mice and compared pharmacokinetic profiles, particularly brain uptake and clearance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of in vitro autoradiography and in vivo PET studies on rat brain, we speculated that insufficient brain permeability of [ 11 C]­QCA might be induced by ATP-binding cassette efflux transporters located at the blood–brain barrier, , particularly, P-glycoprotein (PgP, ABCB1) and breast cancer resistance protein (Bcrp, ABCG2). To test this hypothesis, we carried out PET imaging studies of [ 11 C]­QCA on wild-type and PgP/Bcrp knockout (ABCB1a/1b –/– ABCG2 –/– ) mice and compared pharmacokinetic profiles, particularly brain uptake and clearance.…”
Section: Resultsmentioning
confidence: 99%
“…As we previously reported, , the PET dynamic images were reconstructed using ASIPro VW software (Analysis Tools and System Setup/Diagnostics Tool, Siemens Medical Solutions). Volumes of interest, including the whole brain, cerebral cortex, cerebellum, striatum, thalamus, and pons were placed using ASIPro software.…”
Section: Methodsmentioning
confidence: 99%
“…For pretreatment studies, URB597 (3 mg/kg), SAR127303 (1 mg/kg), JZL184 (3 mg/kg) or KML29 (3 mg/kg) dissolved in 300 µL saline containing 10% ethanol and 5% Tween ® 80 was injected at 30 min via the tail vein catheter before the injection of [ 11 C]SAR127303 ([ 11 C] 5a ) or [ 11 C]TZPU ([ 11 C] 5f ). As we previously reported, 43 the PET dynamic images were reconstructed using ASIPro VW software (Analysis Tools and System Setup/Diagnostics Tool, Siemens Medical Solutions). Volumes of interest, including the whole brain, cerebral cortex, cerebellum, striatum, thalamus and pons were placed using ASIPro software.…”
Section: Methodsmentioning
confidence: 99%
“…Alternative targets to study the ECS by neuroimaging techniques are substrates for enzymes involved in endocannabinoid degradation, transport or synthesis. Two examples are the MAGL ligand [ 11 C]10 (MAGL-0519), which demonstrated high specific binding and selectivity in vitro and in vivo (Cheng et al, 2018) and the radiolabeled reversible FAAH inhibitor [ 11 C]MPPO, which showed moderate uptake with heterogeneous distribution in rodents brain (Wang et al, 2016). Figure 4C depicts the Monte Carlo simulation slice images of the activated thalamus, cerebellum and globus pallidus for the ECS.…”
Section: Neuroimaging Of Cannabinoid Receptorsmentioning
confidence: 99%